Shareholder Wealth Effects: Successful vs. Unsuccessful Bidders - Amporn Soongswang (Journal of Accounting, Business and Management (JABM), 2009)
This study analyses the impact of successful and unsuccessful takeovers, occurring on the Stock Exchange of Thailand (SET) between 1992 and 2002 on bidding firm shareholders' wealth. The firms abnormal returns during a period of twelve months before and after the takeover are measured using the market and market-adjusted models, and three parametric test statistics. The results suggest that the Thai takeovers apparently create values of the successful bidding firm's shareholders. However, they increase and decrease abnormal returns (varied by metrics) to unsuccessful bidding firms. The evidence also shows that prior to the announcement months, both successful and unsuccessful bidding firms are likely to anticipate the takeover news, but the unsuccessful firms are doubtful if the takeover outcomes would be successful.